Coronal origin of the polarization of the high-energy emission of Cygnus X-1 - Romero, Gustavo Esteban (2014)
Context. Cygnus X-1 is the candidate with the highest probability of containing a black hole among the X-ray binary systems in the Galaxy. It is also by far the most often studied of these objects. Recently, the International Gamma-Ray Astrophysics Laboratory Imager on board the Integral satellite (INTEGRAL/IBIS) detected strong polarization in the high-energy radiation of this source, between 400 keV and 2 MeV. This radiation has been attributed to a jet launched by the black hole. Aims. We consider whether the corona around the black hole might be the site of production of the polarized emission instead of the jet. Methods. We studied self-consistently the injection of nonthermal particles in the hot, magnetized plasma around the black hole. Results. We show that both the high-energy spectrum and polarization of Cygnus X-1 in the low-hard state can originate in the corona, without needing to invoke a jet. We estimate the degree of polarization in the intermediate state, where there is no jet, to provide a tool to test our model. Conclusions. Contrary to the commonly accepted view, the jet might not be the source of the MeV polarized tail in the spectrum of Cygnus X-1.